The Predictive Value of the Preoperative Systemic Inflammatory Response Indices in Non–Organ-Confined Disease in Upper Urinary Tract Urothelial Carcinoma - Sung Kyung Choi; Chan Hoon Gwak; Jungyo Suh; Bumjin Lim; Cheryn Song; Dalsan You; In Gab Jeong; Jun Hyuk Hong; Bumsik Hong; Choung-Soo Kim; Hanjong Ahn (Journal of Urologic Oncology)
Purpose This study aims to evaluate the systemic inflammatory response indices (SII) for the prediction of the non–organ-confined (non-OC) disease in upper urinary tract urothelial carcinoma (UTUC) patients. Materials and Methods From March 2010 to March 2020, patients who underwent radical nephroureterectomy (RNU) in a single tertiary center were retrospectively reviewed. Tumor location, multifocality, hydronephrosis on preoperative imaging, and preoperative SII, including C-reactive protein-to-albumin ratio (CAR), neutrophil-to-lymphocyte ratio, and platelet-to-lymphocyte ratio (PLR) were used for analysis. Non-OC defined by locally advanced (pT3-4) or node-positive disease (pN1-2) in pathologic examination. Multivariable logistic regression was used for determining independent predictive markers of non-OC disease. Factors associated with locally advanced (pT3-4), and node-positive (pN1-2) disease were also analyzed. Results Overall, 711 UTUC patients who underwent RNU, without neoadjuvant chemotherapy, were analyzed. The average age was 68.6±9.9 years and 507 patients were male. Non-OC disease was 36.8% (262 of 711); specifically, 35.9% (255 of 711) was locally advanced and 7.2% (51 of 771) was node-positive disease. Multivariable analysis demonstrated hydronephrosis (odds ratio [OR], 1.46; 95%confidence interval [CI], 1.06–2.01; p=0.02), high PLR (OR, 1.45; 95% CI, 1.05–2.01; p=0.03), and high CAR (OR, 2.56; 95% CI, 1.79–3.66; p<0.01) were independent predictive markers non-OC disease. Hydronephrosis (p=0.01), high PLR (p=0.02), and high CAR (p<0.01) were predictive markers for locally advanced disease, and multifocal tumor (p<0.01) and high CAR (p<0.01) were predictive markers for node-positive disease. Conclusions CAR is a novel important factor for predicting any subtype of non-OC disease among SII. Large scale, multicenter studies should validate the clinical role of CAR.